Fast Hollow Fiber Liquid-Phase Microextraction as a Greener Alternative for the Determination of N,N-Dimethyltryptamine and Harmala Alkaloids in Human Urine - Silveira, Gabriela de Oliveira; Lourenço, Felipe Rebello; Bruno, Vitor; Yonamine, Mauricio (Frontiers in Chemistry, 2020)
The ayahuasca tea is an entheogen beverage used for shamanic purposes, prepared by decoction of different Amazonian plants containing dimethyltryptamine (DMT) and harmala alkaloids. Since the therapeutic potential of the tea is being largely studied in the recent years, mainly for the treatment of psychiatric disorders, the determination of the components in human and animal matrices is mostly required. In order to avoid the use of large amounts of toxic solvents seem in traditional sample preparation methods, hollow fiber liquid phase microextraction (HF-LPME) brings a greener and time saving alternative. The present study aims to fully develop and apply a HF-LPME method for the determination of DMT, harmine (HRM), harmaline (HRL) and tetrahydroarmine (THH) in human urine using LC-MS/MS. Fractional factorial and Box-Behnken designs were used to identify and optimize significant method variables. Once optimized, the following method was fully validated: 500 µL of urine is added into a tube containing NaCl followed by the addition of DMT-d6 (IS) and pH adjustment with carbonate – bicarbonate buffer. A fiber segment impregnated with decanol and filled acidic buffer (solution A) is introduced into the system which is stirred during 5 minutes at 2400 rpm. The acceptor phase is collected, dried under nitrogen stream at 50 °C and ressuspended with solution A before injection. Once optimized, validation showed a LoD of 1.0 ng/mL for DMT and 2.0 ng/mL for the harmala alkalois. LoQ was 5.0 ng/mL for all analytes. The method has shown to be linear over a concentration range of 5 ng/mL to 200 ng/mL (r2 ≥ 0.99). Intra-day/inter-day precision and accuracy met the acceptance criteria at three quality control (QC) levels (15.0, 90.0 and 170.0 ng/ mL, n= 6, each). Matrix effect evaluation showed predominant ion enhancement and recovery was above 80%. Dilution factors of 10- and 20-fold had good accuracy. Selectivity studies showed no interferences. Analysis of 8 authentic samples collected from 4 subjects proved method feasibility. A simple, time saving and green alternative for the analysis of DMT and harmala alkaloids in human urine was developed, optimized using design of experiments, fully validated and applied to authentic samples.